2014
DOI: 10.1371/journal.pone.0092854
|View full text |Cite|
|
Sign up to set email alerts
|

Rubber Hand Illusion Affects Joint Angle Perception

Abstract: The Rubber Hand Illusion (RHI) is a well-established experimental paradigm. It has been shown that the RHI can affect hand location estimates, arm and hand motion towards goals, the subjective visual appearance of the own hand, and the feeling of body ownership. Several studies also indicate that the peri-hand space is partially remapped around the rubber hand. Nonetheless, the question remains if and to what extent the RHI can affect the perception of other body parts. In this study we ask if the RHI can alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 28 publications
(50 reference statements)
0
12
0
Order By: Relevance
“…While in all the above-mentioned studies the real and fake hands differed in position but were mostly aligned in terms of orientation, other experiments have shown that BOIs can be induced in presence of an additional mismatch in orientation, provided that the fake body (body part) was seen in an anatomically plausible posture. For example, rotating the fake left hand by 44° clockwise did not prevent participants from experiencing the physical touch as if coming from the position of the rubber one, and further led to a recalibration of their perceived elbow joint angle (Butz et al, 2014 ). BOIs were experienced also when the seen fake hand, rotated away from the real one, crossed the body midline (Brozzoli et al, 2012 ; Perez-Marcos et al, 2012 ); but see (Costantini and Haggard, 2007 ; Cadieux et al, 2011 ) for effects in proprioceptive drifts.…”
Section: Multimodal Triggers and Semantic Constraints In Body Ownershmentioning
confidence: 99%
“…While in all the above-mentioned studies the real and fake hands differed in position but were mostly aligned in terms of orientation, other experiments have shown that BOIs can be induced in presence of an additional mismatch in orientation, provided that the fake body (body part) was seen in an anatomically plausible posture. For example, rotating the fake left hand by 44° clockwise did not prevent participants from experiencing the physical touch as if coming from the position of the rubber one, and further led to a recalibration of their perceived elbow joint angle (Butz et al, 2014 ). BOIs were experienced also when the seen fake hand, rotated away from the real one, crossed the body midline (Brozzoli et al, 2012 ; Perez-Marcos et al, 2012 ); but see (Costantini and Haggard, 2007 ; Cadieux et al, 2011 ) for effects in proprioceptive drifts.…”
Section: Multimodal Triggers and Semantic Constraints In Body Ownershmentioning
confidence: 99%
“…Following this criteria, two specific estimates across all trials were identified and replaced by the average estimate values of their respective condition and estimation task. We chose this amount of participants as our target sample size, because past studies of rubber hand illusion drawn conclusions from 15-30 participants sample size (e.g., Bekrater-Bodman et al, 2014;Butz et al, 2014;Constantini & Haggard, 2007).…”
Section: Methods Participantsmentioning
confidence: 99%
“…Nevertheless, RHI was effective in modulating the perceptual judgments by means of attention to hand-space. Also Butz, Kutter and Lorenz (2014) found that the proprioceptive drift not only adjust the perception of the fixed hand in body-relative space, but includes modification of perception in the relative elbow. Both studies explored the relation between proprioceptive drift and estimates of fixed body-space stimuli, but none of them evaluated these estimates in terms of numerical estimation judgements.…”
Section: Introductionmentioning
confidence: 96%
“…Various researchers have investigated properties of a postural body schema and its plasticity (Holmes and Spence, 2004 ; Cardinali et al, 2009 ; Hoffmann et al, 2010 ; Butz et al, 2010b , 2014 ) 1 . What these treatises all have in common is that temporal predictive sensorimotor structures are learned, which predict sensory changes given motor activities or other sensory dynamics.…”
Section: Progressively Developing Particular Predictive Encodingsmentioning
confidence: 99%